New records of processid shrimps from the Indo-West and East Pacific (Crustacea: Decapoda) - de Grave, Sammy; Anker, Arthur (Zootaxa, 2013)
New records are presented for the caridean shrimp family Processidae in Indo-West and East Pacific waters, based mainly on recently collected material. These records highlight that many processid species may be relatively widespread, although the distribution of some species remains imperfectly known. The colour pattern of several species is here documented for the first time, showing its potential use as an additional identification character. The available information on the ecology of the reported species is summarised.